Sistema embarcado para aquisição de sinais mioelétricos - BATISTA, Kleu William Ribeiro dos Santos (2023)
This work aims to develop a prototype of an embedded system, which is able to perform the acquisition of myoelectric signals from the muscle fiber through a non- invasive technique. The system also performs signal processing usingenanalog filters and amplifiers operational at standard configurations in the literature. The complete system is managed by a PIC 18f4550 microcontroller, which converts the signal from analog to digital and record the data obtained on a micro SD card. Simulations and practical tests are carried out, so that the system reaches the satisfactory result in the final data recorded minimizing errors in the prototype implementation. The results of this work can contribute to the development of other technological applications, such as development of devices to monitor different types of myopathies and help in their treatment, or even for devices such as prostheses, robotic arms and others.